The Development of Information Management Model of Buddhadasa Bhikkhu’s Life and Works for Information Services and Dissemination - Sukkharom, Thanisa (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2018)
Abstract This research aims to (1) analyze and synthesize Buddhadasa Bhikkhu’s life and works; (2) study the procedure of information management for Buddhadasa Bhikkhu’s life and works; (3) investigate the dissemination of Buddhadasa Bhikkhu’s life and works and (4) develop a model of information management for Buddhadasa Bhikkhu’s life and works. This research employed qualitative methods including of documentary analysis, interview and focus group discussion. The research population included 1,065 Buddhadasa Bhikkhu’s printed a work, the representative samples consisted of 47 administrators and staff selected by defined purposive sampling for four Thai organizations responsible for management of information regarding Buddhadasa Bhikkhu’s life and works. A group of 15 experts verified the research design with defined purposive sampling in order to try out the design. The data analysis adopted the analytic inductive method, and the results were presented by the summary and descriptive method. The research findings were as follows : (1) The body of knowledge acquired from the analysis and synthesis of Buddhadasa Bhikkhu’s life and works could be classified into 2 parts, namely Dharma Khot sets and Dhamma Teaching sets, which mainly contained 3 sections, composed of Dhamma for Beginners, Intermediate Dhamma and Advanced Dhamma. These aforementioned contents focused on Anapanasati (Buddhist meditation), cessation of suffering and relieving the burden of selfishness. (2) The information management procedure for Buddhadasa Bhikkhu’s life and works at the agencies studied consisted of information resource management by self-production and donation appeal, Dewey decimal classification, providing heading and indexes, database management, services and dissemination. (3) The services and dissemination of Buddhadasa Bhikkhu’s life and works were basic services, i.e. borrowing and return of information resources, services provided by volunteers, services and dissemination of Buddhadasa Bhikkhu’s life and works for database and websites, and organizing Buddhadasa Bhikkhu-related holy day activities. (4) The management model of information management for Buddhadasa Bhikkhu’s life and works for information services and dissemination was the management of linked data for collaborative information services, consists of sharing information resources, circulating exhibitions and accessing digital information services. Keyword :Information Management, Services and Dissemination, Buddhadasa Bhikkhu’s Life and Works Buddhadasa Bhikkhu’s Information Management